Mass Spectrometric 14C and U-Th Measurements in Coral. Issue 3 (18th July 2016) - Burr, G. S.; Edwards, R. L.; Donahue, D. J.; Druffel, E. R. M.; Taylor, F. W.
Abstract : We discuss U-Th and 14 C measurements in coral. Samples with U-Th dates in excess of 50 ka BP were chosen for study. Some bulk samples from this group have measurable 14 C dates, which range from 30 ka to 43 ka bp. These can be explained by 0.5–2.5% contamination by modern carbon. This small amount of contamination can produce significant offsets in 14 C dates of coral samples older than ≃10 ka. It may be undetectable in X-ray powder diffraction patterns. We describe a sample pretreatment that removes the modern carbon by selective dissolution and produces accurate 14 C dates.